Development of a chemical-kinetic database for the laminar flame speed under GDI and water injection engine conditions. (August 2018) - Cazzoli, Giulio; Falfari, Stefania; Bianchi, Gian Marco; Forte, Claudio
Abstract: The use of direct injection, supercharging, stoichiometric operation and reduction of the engine displacement, necessary to limit the specific consumption without reducing the power, makes the current spark ignition engines sensible to both the detonation and the increase of the inlet turbine temperature. The current research has therefore focused on the study of strategies aimed at reducing the risk of detonation using traditional and innovative solutions such as water injection. The application and optimization of these strategies can not ignore the knowledge of physical quantities characterizing the combustion such as the laminar flame speed. The laminar burning speed is an intrinsic property of the fuel and it is function of the mixture composition (mixture fraction and dilution) and of the thermodynamic conditions. The experimental measurements of the laminar flame speed available in the literature, besides not being representative of the pressure and temperature conditions characteristic of GDI engines, rarely report the effects of dilution by EGR or water vapor. To overcome the limitations of the experimental campaign it is possible to predict the value of the laminar flame speed resorting to numerical combustion models based on chemical kinetics. The increased performance of computing systems makes affordable the use of chemical schemes with a high number of species and reactions without facing an excessive temporal cost. In this work it is presented a methodology for the construction of a laminar flame speed database based on a non-reduced kinetic scheme and an open source solver (Cantera) for a commercial gasoline surrogate under the typical conditions of GDI engines with the addition of the effects of dilution with water and EGR.